Dietary options to reduce the environmental impact of milk production - Wilkinson, J.M.; Garnsworthy, P.C. (Cambridge University Press, 2017)
A range of options was explored to test the hypothesis that diets for dairy cows could be formulated to reduce the carbon footprint (CFP) of feed, increase efficiency of conversion of potentially human-edible feed into milk, increase nitrogen use efficiency (NUE) and reduce methane (CH4) emissions per kg milk. Diets based on grazed grass, grass silage, maize silage or straw, supplemented with raw material feeds, were formulated to meet requirements for metabolizable energy and metabolizable protein for a range of daily milk yields. At similar levels of milk yield, NUE, predicted CH4 emissions and diet CFP were generally higher for diets based on maize silage than for those based on grazed grass, grass silage or straw. Predicted CH4 emissions and human-edible proportion decreased, while NUE increased with the increasing level of milk yield. It is concluded that there is potential to reduce the environmental impact of milk production by altering diet formulation, but the extent to which this might occur is likely to depend on availability of raw material feeds with low CFPs.